The chocolate book bandit [large type] - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2014)
Chocolate shop owner Lee McKinney Woodyard investigates the murder of a retiring member of the library board at a board meeting where all in attendance are suspect.